Chapter La centralità dell'orientamento negli inserimenti lavorativi di persone fragili - Ulivi, Costanza (Studies on Adult Learning and Education, 2022)
The Region of Tuscany, has developed a process/methodology to foster autonomy and accompany to work disadvantaged people and people with disability. The approach adopted consists of an integrated methodology that sees the recipients adhere to a customized project, prepared together with the Social Services, the local Employment Centers and public and private entities active in the field of interventions to combat poverty and social exclusion. Third Sector Entities play a key role in this framework.